NECKCHECK PROJECT: enhancing diagnostic accuracy in oropharyngeal squamous cell carcinoma through computer-based radiological tools - Sara María Ferrero-Coloma; Julián Izquierdo-Luzón; Avelino Pereira-Expósito; Jose Antonio Quesada; Carlos Ferrero-Coloma; Manuela Sancho-Mestre; Elena Garcia-Garrigós; Vicente Gil-Guillen (Scientific Reports)
Abstract The interpretation of radiological images for head and neck tumors often lacks standardized protocols, increasing the risk of diagnostic inconsistencies. This study introduces a computerized radiological checklist designed to enhance diagnostic accuracy and standardize the evaluation of oropharyngeal squamous cell carcinoma (OPSCC) imaging among otolaryngologists (ENTs). A radiological checklist was developed based on a comprehensive literature review and digitized into an intuitive interface. A concordance study involving 15 ENTs was conducted, assessing 90 OPSCC cases in two phases: before and after using the checklist. Diagnostic agreement with radiologists was measured using Cohen’s kappa coefficient, and a mixed-effects linear model evaluated accuracy improvements, accounting for patient sex, age, stage, and HPV status. The checklist significantly improved diagnostic concordance, increasing Cohen’s kappa from 0.28 (95% CI: 0.09–0.46) without it to 0.66 (95% CI: 0.55–0.77) with it (p < 0.01). The mixed-effects model showed a mean improvement of 2.66 correct responses in the checklist group (SE 0.31, p < 0.001). This study supports the effectiveness of this checklist in improving the diagnostic consistency and accuracy of OPSCC imaging. This method shows promise as a practical tool to reduce errors and enhance clinical practice among ENT specialists.